2011 25th Brazilian Symposium on Software Engineering 2011
DOI: 10.1109/sbes.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

SLeSS: A Scrum and Lean Six Sigma Integration Approach for the Development of Sofware Customization for Mobile Phones

Abstract: Resumo-O desenvolvimento de software embarcado para celulares requer um conhecimento profundo dos processos de desenvolvimento, tecnologias e restrições relacionadas com o software e hardware. Além disso, a crescente competitividade desse nicho exige alta produtividade e qualidade. Desta forma, há uma necessidade de investir na melhoria contínua dos processos, na pesquisa de novas tecnologias e metodologias, aumentando o desempenho dos projetos para atenderàs necessidades e expectativas do cliente. Este artigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
0
11
0
8
Order By: Relevance
“…SLeSS [5], is an agile approach that integrates Scrum and Lean Six Sigma that focuses on project management and process improvement for the development of embedded software for mobile phones. The use of SLeSS assists in the easy adaptation to requirement changes in the later stages of the project and with less overall impact than the traditional approach which helps in meeting deadlines, reduces overtime hours, and delivers more rapidly versions and shortening the development cycle.…”
Section: Mobile App Development Methodologiesmentioning
confidence: 99%
“…SLeSS [5], is an agile approach that integrates Scrum and Lean Six Sigma that focuses on project management and process improvement for the development of embedded software for mobile phones. The use of SLeSS assists in the easy adaptation to requirement changes in the later stages of the project and with less overall impact than the traditional approach which helps in meeting deadlines, reduces overtime hours, and delivers more rapidly versions and shortening the development cycle.…”
Section: Mobile App Development Methodologiesmentioning
confidence: 99%
“…Hybrid method engineering approach is a variation of Adaptive Software Development (ASD) which blended the ideas of ASD and New Product Development (NPD) [12]. SLeSS (Scrum and Lean Six Sigma integration approach ) is a variation based on Scrum for the development of embedded software for mobile phones [13]. It pursues a combination of the effort and consistent deliveries of the Scrum sprints with the continuous process analysis and improvement model represented by the Six Sigma methodology: Define, Measure, Analyze, Improve, and Control.…”
Section: Mobile Application Development Methodsmentioning
confidence: 99%
“…Only one academic case study has been reported by Scrum and MDPS. SLeSS has been adopted by a mobile software company to develop custom software for cell phone provider, but no detail has been reported [13].…”
Section: Mobile Application Development Methodsmentioning
confidence: 99%
“…This study was based on 1 case study not related to mobile software. Scrum Lean Six Sigma (SLeSS) is a new approach was developed by da Cunha, et al [28] for the development of embedded software for mobile. This model is integration between Scrum and Lean Six Sigma.…”
Section: Related Researchmentioning
confidence: 99%